1974
DOI: 10.1111/j.1432-1033.1974.tb03690.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of a Purified Non‐Histone Chromosomal Protein with DNA and Histone

Abstract: 1. The interactions of a purified calf thymus chromosomal non-histone protein (designated protein HMGl) with bacteriophage T7 DNA and calf thymus DNA have been investigated by sedimentation analysis in the ultracentrifuge. The results obtained show that (a) the non-histone protein HMGl binds to DNA in an ionic-strength-dependent manner, (b) the DNA can bind up to approximately four to five times its weight of protein HMG1, the protein distributing itself evenly along the DNA chains, and (c) the interaction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0
1

Year Published

1975
1975
1993
1993

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 14 publications
6
50
0
1
Order By: Relevance
“…Given these results, we reasoned that good candidates for the source of the activity in the HeLa extracts are a subset of the HMG proteins. HMG1 and HMG2, like HU, are relatively abundant, bind D N A without sequence specificity, and resist heat and acid treatment (Shooter et al 1974;Goodwin et al 1975;Johns 1982;Kuehl et al 1984;Drlica and Rouvihre-Yaniv 1987). HMG1 and HMG2 are -2 5 kD in molecular mass but migrate at -2 9 kD on SDS-polyacrylamide gels.…”
Section: Hmg Proteins In Hela Nuclear Extract Can Substitute For H U mentioning
confidence: 99%
“…Given these results, we reasoned that good candidates for the source of the activity in the HeLa extracts are a subset of the HMG proteins. HMG1 and HMG2, like HU, are relatively abundant, bind D N A without sequence specificity, and resist heat and acid treatment (Shooter et al 1974;Goodwin et al 1975;Johns 1982;Kuehl et al 1984;Drlica and Rouvihre-Yaniv 1987). HMG1 and HMG2 are -2 5 kD in molecular mass but migrate at -2 9 kD on SDS-polyacrylamide gels.…”
Section: Hmg Proteins In Hela Nuclear Extract Can Substitute For H U mentioning
confidence: 99%
“…[9] of '"1-labelled protein HMGZ with the unlabelled protein HMGZ Preparation of DNA DNA was isolated from bacteriophage T7 by the method described by Lawley et al [3]. Calf thymus DNA was prepared by the method of Kay et al [4].…”
Section: Preparation Of Non-histone Protein Hmg2mentioning
confidence: 99%
“…They possess 40 -50 % a-helix structures which are sensitive to pH as well as urea concentration [3,4]. Shooter et al [2] and Goodwin et al [5] showed that proteins HMGl and HMG2 bound DNA in a similar manner through ionic bonding between the basic amino acid Abbreviation. CD, circular dichroism ; proteins HMG 1 and HMG2, high-mobility-group non-histone proteins 1 and 2. residues and the phosphates of the DNA.…”
mentioning
confidence: 99%